Excusing Inexcusable Acts : Techniques of Neutralization Use By Priests - Hazard, Byron (My University, 2015)
The purpose of this study was to research the effects of neutralization and denial among Chicago and Los Angeles Roman Catholic priests who were accused of sexually abusing minors.
Color poster with text.
Keywords: Neutralization; Priest sex abuse; Roman Catholic church; Posters